Smart Contract in the Metaverse: A Comparative Legal Analysis of Nigeria and Uganda in the Age of Digital Transaction - Aidonojie, Paul Atagamen; Adebayo, Adesoji Kolawole; Eregbuonye, Obieshi; Onwubiko, Kelechi Jude; Damina, Joshua John (Universitas Negeri Gorontalo, 2025)
The emergence of the Metaverse as a decentralized digital ecosystem has transformed traditional contract enforcement by introducing smart contracts, self-executing agreements embedded in blockchain systems. This study conducts a comparative legal analysis of the regulatory frameworks governing smart contracts within Metaverse operations in Nigeria and Uganda. Employing a doctrinal legal method, the research critically examines primary legal sources such as statutory laws and case law, alongside scholarly literature, to assess legal recognition, enforceability, and institutional preparedness. The study reveals a significant regulatory gap in Nigeria, where the absence of a comprehensive legal framework creates uncertainty in the enforceability of smart contracts, despite growing blockchain policy initiatives. In contrast, Uganda has established more definitive legal provisions, particularly through its Electronic Transactions and Signature Acts, which explicitly validate digital contracts. The novelty of this study lies in its regional comparative focus on emerging economies and its analysis of how traditional contract principles interact with decentralized digital platforms. The urgency of this inquiry is underscored by the rapid digitalization of commerce, which necessitates timely legal adaptation to prevent regulatory obsolescence and safeguard stakeholders. This research contributes to the discourse on digital governance by proposing a legal reform agenda for Nigeria, advocating for the adoption of a smart contract-enabling framework modeled after Uganda’s approach. Ultimately, it calls for regional and international harmonization to ensure legal certainty, consumer protection, and dispute resolution within Metaverse-driven economies.